Mark I. answered • 03/31/19

EMT Turned Teacher

I am not sure why nobody answered your question and it probably won't help now. Buuuut, I went ahead and solved it:

Use two kinematic equations: v_{f} = v_{0} + at & v_{f}^{2} = v_{0} + 2aΔx

1st find the final velocity using the second eqn. And, then plug that into the first equation and solve for time.

a = 4.5m/s^{2}

initial velocity= 15m/s

Δx = 45m

v_{f}^{2} = v_{0} + 2aΔx = 15^{2} +2(4.5)(45) = 630=

v_{f} = √630 ≅25.1 m/s

Manipulating our 1st equation we get: (v_{f} - v_{0})/a = t

t = (25.1 - 15)/4.5 = 2.24 s